Measurement of Sustainability of Agriculture in Watershed Environment - K. Atchuta Raju,; J. Dilip Babu,; M. Sudarshan Reddy, (Journal of Agricultural Extension Management, 2025)
The improvement of productivity of agricultural crops is now a days viewed from their sustainability in the fields. In a global conference on "Environment and Development" organized by United Nations under the chairmanship of Brundtland on 1987, the term 'Sustainable Development" was defined as "a development which can last and is different from economic development in sensuo stricto. Development is a comprehensive economic, social, cultural and political process aiming at the constant improvement and the well being of the population and of all individuals on the basis of their active, free and meaningful participation in development. Thus sustainable development is that development which can protect the environment by satisfying the needs of the present generation keeping in view the needs for development for future generations". The concept of sustainable development started sometimes in the late 1970's. This has received wider attention among the planners, policy makers, scientists and researchers across the globe. The reason is increase in population growth and its increase in use and misuse of resources which lead to rapid deterioration of natural resource base through the process like, soil erosion, deforestation, air pollution, ozone depletion and water pollution